Midiatização da religião: processos midiáticos e a construção de novas comunidades de pertencimento : estudo sobre a recepção da TV Canção Nova - Gasparetto, Paulo Roque (Universidade do Vale do Rio do Sinos, 2009)
The study aims at analyzing the phenomena of religion midiatization characterized as “belonging communities”, considering its causes, but above all, it aims at showing the televisive experiences crossing the believers daily lives, displacing them to socializations carried out in the interior of the reportedly socioreligious-televisive community. Religious sense recognition strategies and socio symbolic practices developed by the catholic receivers of the TV Canção Nova, in Caxias do Sul, are shown. The study methodology, consists in showing how the reception relates to the offer, and from this relationship it structures what to us seems to be its specificity on the process of constitution of functioning in the realm of this community. The study carries out the qualitative description and analysis of the empiric material, by considering how a professional of communicational prospection, we seek with love, patience and sharpness, the data to describe the appropriations that the believers carried out on the con
Keywords: complexidade; comunidade de pertencimento; dispositivo; religião; TV canção nova; midiatização; belonging community; complexity; device; religion; midiatization; Ciências Sociais Aplicadas